BIOEFFICACY OF INSECTICIDES AGAINST LEAF WEBBER IN CAULIFLOWER - M.V. NAGESH KUMAR, N. JEMIMAH, G. SRIDEVI V. ANITHA, G. UMA DEVI and (The Journal of Research, PJTSAU, 2021)
Studies on the bioefficacy of various insecticides against cauliflower leaf webber, Crocidolomia binotalis (Zeller) were conducted at College farm, College of Agriculture, Rajendranagar, Hyderabad during rabi, 2018-19 and 2019-20. Insecticides belonging to different groups were selected. Two sprays of the test insecticides were given at 15 days interval during curd initiation stage. Insect counts one day before spray and 3, 5 and 7 days after each spray were recorded. Among the various insecticides tested, chlorantraniliprole proved to be effective in reducing the population of leaf webber after both sprays recording lowest mean larval population of 0.20 larvae/plant at 7 days after second spray during first season followed by spinosad (0.33 larvae/plant), emamectin benzoate (0.33 larvae/plant) and indoxacarb (0.47 larvae/plant) which were on par. During second season, lowest leaf webber population of 0.33 larvae/plant was recorded in chlorantraniliprole treated plot which was on par with spinosad (0.47 larvae/plant), emamectin benzoate (0.47 larvae/plant) and indoxacarb (0.67 larvae/plant). The per cent reduction in different treatments over control at 7 days after second spray revealed that chlorantraniliprole proved to be effective in reducing the population of leaf webber by recording highest overall mean per cent reduction of 84.14 followed by emamectin benzoate, spinosad and indoxacarb with 78.90, 78.46 and 71.22%, respectively.